Influence of Light-Curing Glaze and Chlorhexidine Gluconate in the Acrylic Resin Properties: An in situ Study - Commar, Betina Chiarelo [UNESP]; Silva, Emily Vivianne Freitas da; Penitente, Paulo Augusto [UNESP]; Bitencourt, Sandro Basso [UNESP]; Barao, Valentim Adelino Ricardo; Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP] (Dennis Barber Ltd, 2022)
This in-situ study aimed to evaluate the chromatic stability, microhardness, and surface free energy of chemicaly activated acrylic resin (CAAR) samples. Eighty CAAR samples were made and each volunteer (n = 20) received two palatal plates with two sides of groups (without and with glaze application). The samples were exposed to two conditions: the control condition (sucrose 30%) and the test condition (sucrose 30% and 0.12% chlorhexidine). The volunteers used the first palatal device (control condition) for seven days and the second palatal device (test condition) for another seven days, with a seven-day break between them. Then, the Delta E-00 , microhardness, and surface-free energy tests were performed. Analysis of Variance and the Tukey test were used (alpha = 0.05). The control group with glaze showed higher Delta E-00 compared to the group without the glaze. The test group with glaze had less Delta E-00 than their respective controls. In both periods, when the glaze was applied, higher microhardness values were found for al groups. Groups with glaze showed lower roughness and higher surface-free energy than groups without the glaze. The values obtained in this study were satisfactory, showing the clinical efficacy of glaze and the use of 0.12% CH for maintaining the physical and mechanical properties of CAAR.
Keywords: Hardness; Surface Property; Acrylic Resin; Temporary Dental Restorations